Owner Estimate of Rig Contracts in Oil and Gas Business According to Legal Certainty Principles - Radjagoekgoek, Robert Pangihutan (Law Review, 2023)
As one of the vital and strategic natural resources and vital role that impact society, oil and gas is one of state revenue sources to support national development. To implement Article 33 of the 1945 Constitution, to obtain people welfare and prosperity, Oil and Gas Law No 22, 2001 mandated Special Task Force for Upstream Oil and Gas Business Activities to oversee upstream activity done by oil and gas contractors. Contractors conduct rig procurement processes with their Owner Estimate in alignment to Presidential decree No 12, 2021 and Summary of Procedural Guidelines of 007, 2017.By this reason, legal certainty is needed to deal with problems at implementation level. Two legal issues research, regulation and preparation implementation of Owner Estimate  Value in Rig contract. The research analysis is using normative juridical which are supported by empirical studies. Owner Estimate  preparation guidelines provide multiple interpretations, inconsistencies and a legal vacuum. In practice, problems related to aspects of legal certainty, Owner Estimate offers are not confidential and/or confidential, extreme price cut due to offers below 80% of Owner Estimate are being allowed, the existence of negotiations even though the price offer is already the lowest and below Owner Estimate . It opens for conspiracy in the procurement. It is necessary to amend Perpres and Procedural Guidelines of Special Task Force for Upstream Oil and Gas Migas Number 007 achieving compliance to the principles of agreement, legal certainty and fair business. Regulation change will provide legal certainty, efficiency and effectiveness so Special Task Force for Upstream Oil and Gas Migas, oil and gas contractors and Rig Providers can conduct upstream business activities properly, optimally to support Indonesian social welfare.